If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + -11 + -2 = -13 Reorder the terms: -11 + -2 + 2n = -13 Combine like terms: -11 + -2 = -13 -13 + 2n = -13 Add '13' to each side of the equation. -13 + 13 + 2n = -13 + 13 Combine like terms: -13 + 13 = 0 0 + 2n = -13 + 13 2n = -13 + 13 Combine like terms: -13 + 13 = 0 2n = 0 Solving 2n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '2'. n = 0 Simplifying n = 0
| 7x+3+2=-33 | | 9x-12=36 | | -9x+6x-1=0 | | .50t+2=16 | | 2n-11-2= | | 2*8-11-2= | | 4x-16=2(x+3) | | 2*8-11-2=13 | | 30=-5(6l+6) | | 2x-8x=5x+10-9 | | -5(4r+1)+2r=-5+5r | | 10*11= | | 10*3+3y=30 | | 3x+1*x=30 | | (S+3)+48-5=s+2 | | 5x=153 | | 19=2.5+4.5n | | 6h+10c+4f=66 | | X+(x*.0825)=350 | | -25-n=2(3n-2) | | -8-6x=14-7x | | 52=4(-2x+3) | | -2x+5y=-54 | | 2x(x-3)(x-2)= | | 5-4x-3=-4 | | 3h+2c+f=19 | | -3(2x+4)=24 | | -4(x-2)+x=-4 | | 5x+3-2x=3x+10 | | 348.16+16.96+11.01=y | | 9=-9-2x | | 3x(x+2)(x+4)= |